06 KARAKTERISTIK SOSIAL EKONOMI DAN KINERJA PENYULUH TERHADAP PELAKSANAAN TUGAS POKOK PENYULUH PERTANIAN DI KABUPATEN MAROS - Jurnal Agribis; Wawan Indrawan; Zulkifli Zulkifli; Azisah Azisah (Universitas Muslim Maros, 2020)
This research was conducted in 4 districts namely Tanralili, Simbang, Bantimurung and Camba Districts, Maros Regency. To choose districts to use (multi stage sampling). To choose a sample in the sub-district, direct appointment is used. There are two data used, namely: primary data, namely data obtained from observations through direct interviews and also through the help of questionnaire lists and secondary data, namely data obtained from agencies / institutions that are related or related to this research. The purpose of this study is: Knowing the socio-economic characteristics of the instructor, namely, age, level of education, length of being a counselor, understanding the local language, the number of family dependents, extension workers' salaries, total income and distance of residence to the place of duty with the implementation of the basic agricultural extension tasks of Maros Regency, Knowing the performance of basic agricultural extension work in Maros district. Data was collected from the survey results using a questionnaire and supplemented with observations / field observations. The data that has been collected is then tabulated to obtain real data used for analysis. This study uses a quantitative descriptive analysis method to determine the level of implementation of basic tasks and the performance of extension workers in Maros Regency. The results of the study can be seen that the social characteristics of the economic instructor with the implementation of the basic agricultural extension work in Maros Regency are age, level of education, length of being an extension agent, understanding the local language, number of family dependents, extension agent's salary, total income, and distance of residence to the place of assignment. high categorization and performance of agricultural extension principal tasks in Maros Regency are in average high category with a percentage value of 86.36%.